Industrial West - February 26, 1898 - (:unkn) unknown (My University, 1898)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
The Industrial West was a newspaper in Clarendon, Texas that resulted from a name change of the Clarendon Weekly Traveler in 1891. The newspaper was published under this name until 1903 when it changed names to the Clarendon Chronicle.
Keywords: Industrial West; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.